Rethinking the duties of a receiver and powers of directors of companies in receivership under Nigerian law (2015)
Receivership is an enforcement procedure devised by Law to ensure that a charged security is realized by debenture holders. The advantages of appointing a receiver are quite enormous and have come to be preferred to other forms of enforcement procedures available to debenture holders. The appointment, qualification and disqualification of receivers in Nigeria as provided by the Companies and Allied Matters Act, CAP C20 Laws of the Federation of Nigeria, 2004 (CAMA) is not only inadequate but unfortunately constitutes an avenue for encouraging incompetent receivership practice. This paper critically examines the role and duties of the receiver in Nigerian law and points out the discrepancies, total lack of regulation and great gaps in the law which has led to great injustice to companies. The paper argues that directors of companies under receivership are not thereby paralysed and they should exercise their powers to monitor the activities of the receiver. There is need to amend the law to streamline the duties of the receiver, provide for regulation of receivership and protection of the company and debenture holders.